Designing a Cloud-Based Ubiquitous Learning Environment for a Hybrid University Language Course - Aom Thai; Rit Som; Ming Kiri; Rustiyana Rustiyana (Yayasan Adra Karima Hubbi, 2025)
Background. The rise of hybrid learning models in higher education has highlighted the need for flexible, scalable, and context-aware digital learning environments capable of supporting continuous language learning beyond classroom boundaries. Purpose. This study aims to design and evaluate a cloud-based ubiquitous learning environment tailored for a hybrid university language course to enhance learner autonomy, engagement, and communicative competence. Method. Employing a design-based research methodology, the study involved iterative cycles of analysis, design, implementation, and evaluation with 42 undergraduate language learners. Data were collected through system usage analytics, pre- and post-course proficiency assessments, and learner experience surveys. Results. The results indicate significant improvements in vocabulary retention, listening comprehension, and task-based communication skills, accompanied by increased learner satisfaction with the flexibility and responsiveness of the system. Conclusion. The study concludes that a cloud-based ubiquitous learning environment can meaningfully enhance hybrid language instruction by integrating mobility, accessibility, and real-time support into traditional course structures.